English for Specific Purposes: Brief History and Definitions - González Ramírez, Carolina (2015)
English for Specific Purposes was born in the 1960s as a technical texts-analysis area. The study of language use over language form strengthened at the end of the decade and materials development became a popular trend. The 1970s and 1980s witnessed the consolidation of the movement in the emphasis on language skills and booming research. Central concepts such as genre, rhetorical moves and expert consultant were introduced. Research has boomed in the last 20 years, specially in the international context, where new journals and vast submission of papers have shown the increased importance of ESP. The evolution ESP and its definitions have developed hand by hand. Seen as an approach by some and a dis- cipline by others and displaying changing characteristics of variables, ESP has and will always shape itself to meet learners’ specific professional or vocational language needs and thus possesses immediate relevance and validity, for as stat- ed by Harding (2007), ESP teaches “the language for getting things done” (p. 6).